PENGARUH PENGGUNAAN POP UP BOOK DIGITAL TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN PESERTA DIDIK KELAS IV PADA MATA PELAJARAN BAHASA INDONESIA - Aprilia Windiyani, Indah; Destini, Frida; Fitriadi; Yulistia, Annisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study was the low reading comprehension ability at SD Negeri2 Gedong Air, particularly in understanding the content of the text, finding the mainidea, identifying important information, and retelling the text in their own words. Thisstudy aimed to determine the effect of using digital pop-up book media on thereading comprehension ability of fourth-grade students in the Indonesian languagesubject. This study used a quantitative approach with a quasi-experimental methodand a nonequivalent control group design. The population of the study consisted of122 students, and the sample included classes IV C and IV D totaling 62 students.The sampling technique was purposive sampling. Data collection techniquesincluded test and non-test methods. The results of the study indicated that therewas an effect of the use of digital pop-up book media on the reading comprehensionability of fourth-grade students in the Indonesian language subject at SD Negeri 2Gedong Air. This was supported by hypothesis testing using a simple linearregression test, which yielded a significance value of 0.000 < 0.05; therefore, H₀was rejected and Hₐ was accepted.